Impacts of cetaceans on the structure of Southern Ocean food webs - Ainley, D; Ballard, G; Blight, LK; Ackley, S; Emslie, ST; Lescroel, A; Olmastroni, S; Townsend, SE; Tynan, CT; Wilson, P; Woehler, E (Marine Mammal Science, 2010)
Recently, Ballance et al. (2006) revived the hypothesis that cetaceans were a majorforce in the structuring of Southern Ocean food webs, and suggested that they arestill playing a keystone role even as their loss continues (see also review in Mori andButterworth 2006), a subject that we herein would like to emphasize. Accordingto this hypothesis, following 60 yr of directed industrial whaling (Tnnessen andJohnsen 1982, Baker and Clapham 2002), the demise of the great whales (blue,Balaenoptera musculus intermedia; fin, B. physalus; and humpback, Megaptera novaeangliae)led to changes in populations and demographic parameters among penguins,seals, and minke whales (B. bonaerensis; see also Laws 1977, Bengtson and Laws1985). These changes to populations of the great whales competitors came aboutupon release from trophic competition as a result of the krill surplus that ensued(i.e., of Antarctic krill, Euphausia superba; Bengtson and Laws 1985).